POTENSI BAKTERI ASAM LAKTAT ISOLAT LOKAL SEBAGAI AGENSIA PROBIOTIK DAN KETAHANANNYA PADA PROSES SPRAY DRYING - Yogeswara, Ida Bagus Agung; Rahayu, Endang S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Lactic acid bacteria are the most important bacteria in food fermentation technology. Lactic acid bacteria can use for functional purpose such as development in probiotic products. Indonesia has so many traditional foods that fermented by lactic acid bacteria and has a potential as a probiotics. In order to preserve probiotics cultures, spray drying was use for this purpose. The objective of this study was to evaluate the probiotics potential from lactic acid bacteria isolated from Indonesian fermented foods and itâs resistance during spray drying. Ten isolate was tested for its antimicrobial activity against five pathogenic bacteria i.e A. hydrophilla, S. typhii, S. dysentri, E. coli OK111 and E. coli stable toxin. All lactic acid bacteria were able to inhibit pathogenic bacteria except for A. hydrophilla. S. dysentri was more susceptible bacteria, followed by E. coli OK111, E. coli stable toxin and S. typhii. All isolates were resistant to bile salts solution up to 3% during 4 and 6 hours of incubation. During exposure in simulated gastric juice, all isolates cannot survive in simulated gastric juice pH 1,5 in 4 and 6 hours incubation. All isolates were tolerant in simulated gastric juice pH 2,0 and pH 3,0 during 4 hours of incubation. Three isolate produce plasmid. Best protection was given by skim milk on L. plantarum Dad 13 and L. plantarum Mut 7 gives a reduction 2 log cycle, and also skim milk protects L. plantarum Dad 13 and L. plantarum Mut 7 from bile salts (1,5%) and simulated gastric juice (pH 2,0) after spray drying during 6 hours of incubation. Storage under high moisture (RH 75 and 90) increase water content and water activity of dry culture and also decrease the number of lactic acid bacteria during storage.